Analysis of the Impact of The Covid-19 Events on Stocks on the LQ45 Index for the January - March 2020 Period - Suci Hayaty; Brady Rikumahu (Program Studi Manajemen, Fakultas Ekonomi, Universitas Langlangbuana, 2022)
In the world of capital markets, indicators are used to measure changes in stock prices. A stock index is an indicator to see information about stock price movements. The existence of various information both from within the country and abroad is one of the external factors that causes the movements of stock prices to change significantly. This study aims to analyze the price movements of the companies' shares included in the LQ45 Index from the impact of a big event that is currently happening, namely the pandemic Covid-19. This study uses the method of Survival Analysis with the approach Kaplan Meier, variable of this study uses stock prices. The results of the research that have been conducted found that external factors, namely information about Covid-19 that spread throughout the world, given a negative impact on stock price movements on the LQ45 Index, namely 45 LQ45 companies experienced a decline in stock prices during the observation period, 5 of 45 companies still experienced a declined. After the observation period took place, viewed by sector, eight sectors included in LQ45 experienced a decline in stock prices at the same time during the period 02 January to 31 March 2020.